Prototype Of Wheel Suggestion Control Using Android Based On Arduino Uno R3 - Maulana Hidayat, Rizki; Hadi Purwanto, Eko; Kristus Pramuko, Andik Ekok (Jurnal Inovatif : Inovasi Teknologi Informasi dan Informatika, 2022)
Development of a wheeled suitcase prototype with arduino-based technology, so that the suitcase can run using its own Android to move the wheeled suitcase. The suitcase control method can use Gesture mode, namely the buttons that have been provided on Android to move the wheel. There is also a Gyroscope, which is a sensor used to track rotation or rotation of the movement device. In other words Gyroscope is referred to as a device that is used to maintain the orientation of an angle to remain stable. The experimental method of this research aims to make observations that are interconnected between cause and effect. After testing the wheeled suitcase using Gesture Mode in this study using the buttons provided by android to move as it should, and for Gyroscope Mode by maintaining the orientation of the android so that the suitcase moves according to the movement of the android. In testing the author has tested the distance of the android connection to the wheeled suitcase, the results obtained are a distance of 7 meters and it is still connected.